Gender Earnings Gap among Urban Youth Adults in Bangladesh: A Comparative Static Analysis - Muhammad Shahadat Hossain Siddiquee; Md. Saiful Islam; Md. Raied Arman (Research in Applied Economics, 2024)
Despite the importance and recognition of young women’s engagement in income-generating activities for socio-economic development, the gender earnings gap still persists across countries, especially in developing countries like Bangladesh. This study presents two datasets from the most recent past to provide fresh evidence for Bangladesh’s urban labor market that has yet to be closely studied. Using individual-level data from the BBS’s (Bangladesh Bureau of Statistics) Labour Force Surveys (LFS) conducted in 2010 and 2015, we have explored the gender earnings gap among the youth (aged 18 to 35 as per Bangladesh’s National Youth Policy 2017) working and earning in the urban labor markets of Bangladesh by applying the three approaches: Mincerian regression, Oaxaca-Blinder decomposition and Quantile regression. The first approach confirms that young women earn significantly less than young men in the urban labor markets after controlling the influences of the covariates. The detailed decomposition results of the second approach indicate that gender differences in hours worked, education, firm characteristics and locations also contribute to the gender earnings gap and the market discrimination against the youth women’s earnings remain the same over the years. The third approach using the lens of distribution perspective shows that earnings gaps persist up to the 25th percentile of distribution in 2010 though it persists across the entire earnings distribution in 2015. The results suggest that engaging more women in income-generating activities, increasing the number of hours worked, improving access to higher education and creating enabling working environment for women might reduce the gender earnings gap.